Development of an Educational YouTube Channel: A Collaboration between U.S. Agricultural Safety and Health Centers. Issue 1 (2nd January 2021) - Wickman, Amanda; Duysen, Ellen; Cheyney, Marsha; Pennington, Whitney; Mazur, Joan; Yoder, Aaron
ABSTRACT: Objectives : The National Institute for Occupational Safety and Health (NIOSH) Agriculture, Forestry, and Fishing Centers (AFF Centers) collaborated to initiate a joint YouTube channel in order to raise awareness of agricultural, forestry, and fishing occupational hazards; provide information to prevent AFF injuries and illnesses; increase the visibility and influence of the AFF Centers; and establish a collaborative model that can be replicated by other organizations. Methods : The collaborators sought to produce a structured channel with high scientific standards. Policies, procedures, and a standard review process were established. Representatives from the AFF Centers coordinated the review process and the procedures by which videos were uploaded to the site. A marketing plan was created including a press release and ideas to promote new videos. Promotions are targeted to agricultural cooperative extension agents, educators, producers, owners, operators, first responders, families and community organizations. Viewership was tracked using YouTube metrics. Results : The site was launched in November 2013. Over a 6-year period, the channel grew from 48 videos to 125 videos with over 10, 500 cumulative watch time hours. The channel is promoted by the AFF Centers through email, social media, conference presentations and outreach exhibits. The channel is also publicized during coordinated national outreach events. Conclusion : Each AFF Center benefitted from increased exposure of their content and the collaboration provided an opportunity to achieve labor efficiencies. YouTube metrics demonstrated that coordinated marketing increases views, watch time and subscriptions. In addition, the success of the channel communicates the benefits to collaboration among organizations with common missions.